Using secure messaging to update medications list in ambulatory care setting. Issue 10 (October 2015) - Raghu, T.S.; Frey, Keith; Chang, Yu-Hui; Cheng, Meng-Ru; Freimund, Sharon; Patel, Asha
Highlights We assess differences between users and non-users of secure messaging for medications list update. Overall, secure message response rate was significantly lower than that for phone call based requests. Response rate was highest among patients aged 41–70 and lowest among patients aged over 70. The time to complete medication list update was similar for secure messaging and phone call requests. Mixed mode communication with patients should continue to be the norm in outpatient settings.